2002
DOI: 10.1556/avet.50.2002.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation decreases total thyroid hormone concentration in small ruminants

Abstract: The effect of dietary zinc (Zn) supplementation on plasma Zn and serum thyroid hormones was evaluated in healthy male Merino lambs and Angora goats. A total of 12 lambs and 12 goats were divided into two equal groups as control and Zn groups in separate experiments. The lambs and goats of the control groups were fed basal rations alone. The Zn contents of these rations prepared for lambs and goats were 40 mg/kg and 35 mg/kg in dry matter (DM), respectively. Both species of animals in the Zn groups were fed a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
9
1
1
Order By: Relevance
“…It indicated that supplemental zinc either from inorganic or organic sources did not infl uence plasma T 3 and T 4 concentration in crossbred calves. Contrary to above Kececi and Keskin (2002) in lambs observed reduced concentration of serum T 3 and T 4 on supplementation of 290 mg Zn kg -1 diet. Th e mean concentration of plasma insulin exhibited non-signifi cant (P>0.05) variation among dietary treatments.…”
Section: Resultscontrasting
confidence: 71%
“…It indicated that supplemental zinc either from inorganic or organic sources did not infl uence plasma T 3 and T 4 concentration in crossbred calves. Contrary to above Kececi and Keskin (2002) in lambs observed reduced concentration of serum T 3 and T 4 on supplementation of 290 mg Zn kg -1 diet. Th e mean concentration of plasma insulin exhibited non-signifi cant (P>0.05) variation among dietary treatments.…”
Section: Resultscontrasting
confidence: 71%
“…Interrelationships among copper and iodine and thyroid hormones were studied in rats by Esipenko and Marsakova (1990) and Aurthor et al (1996). Kececi and Keskin (2002) reported a significant negative correlation between zinc concentration of erythrocytes and serum thyroid hormones in healthy male Herino lambs and Angora goats.…”
Section: Discussionmentioning
confidence: 96%
“…While the mean concentration of total T4 kept constant through the course of the study. Kececi and Keskin (2002) reported that lambs and goats in the Zn groups (40 mg/kg DM for lambs and 35 mg/ kg DM for goats) had significantly higher (P < 0.05) in plasma Zn values than the control one. Contrary to the above results Mandal et al (2008) indicated that supplemental zinc either from inorganic or organic sources did not influence plasma T3 and T4 concentration in crossbred calves.…”
Section: Blood Metabolitesmentioning
confidence: 92%